Oxymorphone active uptake at the blood–brain barrier and population modeling of its pharmacokinetic–pharmacodynamic relationship. Issue 9 (5th March 2013) - Sadiq, Muhammad Waqas; Boström, Emma; Keizer, Ron; Björkman, Sven; Hammarlund‐Udenaes, Margareta; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract The aim of this study was to characterize the blood–brain barrier (BBB) transport and pharmacokinetics–pharmacodynamics (PKPD) relationship of oxymorphone and to further elucidate its possible contribution to oxycodone analgesia. The BBB transport of oxymorphone was studied using microdialysis in male Sprague–Dawley rats. Samples from microdialysis blood and brain probes, brain tissue, and plasma were analyzed by liquid chromatography with tandem mass spectrometry. The effect was measured as tail‐flick latency. The study consisted of a PKPD experiment with combined microdialysis and antinociceptive measurements (n = 8), and another antinociceptive effect experiment (n = 9) using a 10 times lower dose. The combined data were analyzed with an integrated PKPD model in nonlinear mixed effect modeling utilizing a specific method (M3) for handling missing PD observations. The concentration of unbound oxymorphone was higher in brain than in blood, with a ratio of 1.9 (RSE, 9.7%), indicating active uptake at the BBB. The integrated PKPD model described the oxymorphone BBB transport and PKPD relationship successfully, with an EC50 in the brain of 63 ng/mL, and the M3 method was able to address the issue of censored observations. Oxymorphone has active uptake transport at the BBB in rats, with moderate uptake clearance to the brain. Its contribution to analgesia after oxycodone administration is not significant. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3320–3331, 2013